The THE EFFECT OF CORPORATE GOVERNANCE POLICY ON FINANCIAL PERFORMANCE IN THE BANKING SECTOR IN INDONESIA - Kurniawati, Jeanissa Asna; Mulyati, Sri (Jurnal Daya Saing, 2025)
This study investigates the impact of key corporate governance mechanisms—namely institutional ownership, the proportion of independent commissioners, and the presence of an audit committee—on the financial performance of conventional banks in Indonesia. This study aims to analyze the effect of institutional ownership, the proportion of independent commissioners, and the audit committee on financial performance in the conventional banking sector in Indonesia. Financial performance is measured using Return on Assets (ROA). This research employs a quantitative method with multiple linear regression analysis. The sample consists of 21 conventional banks listed on the Indonesia Stock Exchange for the 2019–2024 period, selected through purposive sampling. The results show that institutional ownership has no significant effect on financial performance. In contrast, the proportion of independent commissioners has a positive and significant effect on financial performance, while the audit committee has no significant effect. Simultaneously, all three variables significantly affect financial performance. These findings highlight the crucial role of independent commissioners in strengthening oversight and corporate governance to improve the financial performance of banks in Indonesia.